FIGURES OF SPEECH IN THE JINGLE OF CHILDREN’S MILK ADVERTISEMENT: A CASE STUDY IN INDONESIA - Gunawan, Hero; Nadeak, Jessica Naomi; Pratiwi, Maydi Cici; Fauzi, Diaz Ahmad; Siddiq, Muhammad Haichal Juan; Saputra, Hersa Azhar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research deals with figures of speech found in the jingle of children's milk advertisement, case study in Indonesia. The research using qualitative description method and the object of the study is jingles milk advertisement. The source of data were gathered by YouTube observation. An author conducted several research steps such as; collecting data, watching advertisements (either through television/youtube), finding the transcripts, making data sheets, and categorizing data into data sheets. The data were analyzed by using Stylistic theory, which consist of twelve figures of speech:metaphor, metonymy, personification, simile, synecdoche, paradox,litotes, hyperbole, parallelism, anaphora, alliteration, repetition. The result of this study shown that metaphor, repetition, and hyperbole are used in the jingles of children's milk advertisements. The result of the research shows that figures of speech deeply influence jingle's. This study is important to find out the kinds of figures of speech that are used in the advertisements jingle. By analyzing these figures of speech, it is expected that people who read this paper will be comprehend more about figure of speech, they will be easier know kinds of figures of speech and figures of speech of in a jingle hold a very important role in attracting children's attention.